Environmental assessment and perception of the Mindu sources park: subsidies for its conservation (Research, Society and Development, 2020)
The environmental issue has become an important question, making that strategies have been created to reduce man's actions on the environment, where the Conservation Units have their place. For this, the environmental perception of individuals about these spaces must be observed, under penalty of the adopted measures becoming fruitless. The aim of this work was to evaluate the environmental conditions and the perception of the residents around the Nascentes do Mindu park, evaluating the environmental state around the park, the residents' perception and to propose actions for better space management. For this, walks were carried out around the park looking for environmental impacts and interviews with families were made. The absolute values were converted into relative and the damages were mapped and discussed. Families have a low to medium level of education and income, with a household density higher than the national average. Most showed satisfaction in living close to the park and, despite the majority not participating in activities developed in it, they see the space as an opportunity for leisure and preservation. The lack of security and the accumulation of waste in the surroundings were identified as the main problems. “Addicted trash”, sewage discharge and potential risks were identified, requiring greater support from the park and city hall management in combating illegalities, expanding environmental actions and communications, as well as promoting more activities that can sensitize residents about the importance of the reserve to the community.